2023
DOI: 10.1371/journal.ppat.1011340
|View full text |Cite
|
Sign up to set email alerts
|

Roles of long non-coding RNAs in plant immunity

Abstract: Robust plant immune systems are fine-tuned by both protein-coding genes and non-coding RNAs. Long non-coding RNAs (lncRNAs) refer to RNAs with a length of more than 200 nt and usually do not have protein-coding function and do not belong to any other well-known non-coding RNA types. The non-protein-coding, low expression, and non-conservative characteristics of lncRNAs restrict their recognition. Although studies of lncRNAs in plants are in the early stage, emerging studies have shown that plants employ lncRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 222 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that RNA pol IV and V play a role in silencing, plant growth, development, response to environmental changes or plant immunity [4][5][6][7][8][9][10][11][12][22][23][24]. Therefore, we can speculate that the regulation of the gene expression of these RNA pols could be expected in response to some growth conditions.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…It has been demonstrated that RNA pol IV and V play a role in silencing, plant growth, development, response to environmental changes or plant immunity [4][5][6][7][8][9][10][11][12][22][23][24]. Therefore, we can speculate that the regulation of the gene expression of these RNA pols could be expected in response to some growth conditions.…”
Section: Discussionmentioning
confidence: 95%
“…Taken together, these data suggest that RNA pol IV and V may play a major role in early fruit development steps. As RNA pol IV and V have been proposed to participate in the transcription of lncRNAs [24,[31][32][33][34][35][36][37][38], we can speculate about a transcriptional response by these types of transcripts during this development process.…”
Section: Expression Profile During Fruit Developmentmentioning
confidence: 97%
See 2 more Smart Citations
“…used CRISPR‐Cas9 to edit the promoter of CLE genes to enhance grain‐yield‐related traits in maize. [ 146 ] For lncRNAs that are considered to play vital roles in plant immunity and diverse plant‐microbe or insect interaction, [ 152 ] two lncRNAs were mutated with the CRISPR‐Cas9 system, leading to a negative effect on aphid resistance and a decrease of jasmonic acid content. [ 151 ] However, high‐throughput CRISPR library interrogation of these elements in plants has yet to be reported, and only one such study was found to be carried out in Bombyx mori targeting promoters with a large‐scale sgRNA pool.…”
Section: Future Perspectivementioning
confidence: 99%